CIORAN ET LA PHILOSOPHIE EXISTENTIELLE DE LEON CHESTOV - SERES, Sándor (Studia Universitatis Babeș-Bolyai Philosophia, 2019)
Cioran and the Existential Philosophy of Lev Shestov. Cioran is said to have been influenced by Pascal, Kierkegaard and Nietzsche, the author of La Chute dans le temps, thus enrolling in the line of existential philosophy. Much less - or not at all - is mentioned in this context Lev Shestov, who exerted a considerable influence on the intellectual environments in France, but also in Romania, in the period immediately following the First World War. Cioran considered Shestov as one of his spiritual masters, the influence of the Russian thinker being present both in his youthful writings and in those written later in France. We will try to highlight some of Shestov’s ideas which have been creatively taken over by Cioran and that can be found constantly throughout his work.